Reconstruction of upper cervical spine and craniovertebral junction - Suchomel, Petr.; Choutka, Ondrej; Hradil, Jan.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
An illustrative manual for general spine surgeons, this text atlas covers all currently available techniques of upper cervical spine and craniovertebral junction reconstruction. All the surgical risks and benefits are discussed and compared with the outcome of more than 300 surgeries of this region. The surgical procedures are demonstrated step-by-step in instructive drawings and illustrations describing the approach, technique of implant introduction and spine reconstruction. A special focus is on realtime and virtual navigation techniques as well as potential complications and their avoidanc.
Surgical anatomy -- Biomechanical remarks -- Special radiology -- Surgical approaches -- Basic principles of reconstruction techniques -- Specific reconstruction techniques of upper cervical spine and craniovertebral junction -- Virtual and real time navigational techniques -- Traumatic atlantooccipital dislocation (AOD) -- Occipital condyle fractures -- Atlas fractures -- Odontoid process fractures -- Fractures of the ring of axis (hangman type fractures) -- Miscellaneous C2 fractures -- Multiple fractures of axis and atlas-axis fracture combinations -- Acute traumatic atlantoasial dislocation (AAD) in adults -- Posttraumatic deformity -- Non-specific inflammation -- Rheumatoid arthritis -- Tumors -- Congenital and developmental abnormalities -- Degenerative disorders -- Surgical failures.
Electronic reproduction.
Keywords: Spine -- Surgery; Electronic books